OATS‐BEKATUL SEBAGAI PANGAN FUNGSIONAL - Laras Ayni Widyastuti, Wahyu Ardian Nugroho, dan Adhy Putri Rilianti (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research is motivated by the condition of Indonesia as the country with the mainsector of agricultural produce and processed products of rice bran are abundant innumber. The purpose of this analysis, oats and rice bran packed into a new functional food inthe form of oats, bran that have nutritional value in order to effectively meet the nutritionalintake for the whole society.This study was designed with the experimental method. Oats‐Bran categorized asfunctional foods because when processed, can be modified rice bran into foods that havemore interesting colors, good taste, and rich in nutrients that provide a good physiologicaleffects for the body in terms of food consumed as functional. Thus, oats, bran is expected tobe a new breakthrough in the world of functional foods that have met the threerequirements of functional food.Based on laboratory test results, it can be concluded that the protein content isgreater than the glucose content and a relatively low Amylum.Keywords: Bran, Oats, Functional Food